Mandibular advancement devices as a treatment for obstructive sleep apnea: a literature review - Laquihuanaco Coarita, Gina Maritza (2025)
Obstructive sleep apnea (OSA) is a sleep disorder resulting from the narrowing and collapse of the upper airway. It has been associated with an increased risk of motor vehicle accidents, diabetes, and cardiovascular diseases, making it a major public health issue. In recent years, intraoral mandibular advancement devices have gained popularity as an option for the treatment of snoring and OSA. These devices are well tolerated by most patients, and their therapeutic efficacy has been widely demonstrated. Against this background, it is important to know the advantages of their use, the treatment protocol, and their possible side effects.